Hiking fatalities on Angels Landing Trail — factors identified from Zion National Park - Heggie, Travis; Hawkes, Amanda; Küpper, Thomas (Health Promotion & Physical Activity, 2025)
Hiking is a popular outdoor activity with approximately 45 million participants in the United States each year. The growing popularity of hiking has given rise to an increasing number of hiking-related deaths. Within the U.S. State of Utah and Zion National Park, the Angels Landing Trail has been identified as a trail recording a high number of hiking deaths. The popular trail ascends 454 m and is lined with slippery edges and steep drop-offs along its 8 km roundtrip trail. The most minor mistakes will easily result in death. Utilizing a case study approach, this study identified unsafe hiking behavior, pre-existing health conditions, the physical environment, and the social environment as primary contributing factors in hiking fatalities on the trail. In the 1950s – 1960s guard rails were added to the trail, in 2010 a total of 55 meters of posts and chains were installed along the trail, and in 2022 Zion National Park instituted a permit system aimed at reducing overcrowding and improving the hiking experience. Since 2022, only a single hiking death has been recorded on the trail. Further monitoring of the trail is warranted so that of the number of fatalities and the factors contributing to any death can be compared from before and after the implementation of the permit system.